Study on Electrical Performance of High-voltage Disconnecting Switch on EMUs in Extremely-cold Circumstance - WANG Xiongbo; LI Tao; JIANG Congjian; LI Jing (机车电传动)
Main structure and working principle of high-voltage disconnecting switch used on EMUs in extremely-cold circumstance was introduced. Electrical performance of high-voltage disconnecting switch was described, and parameterized calculation was used in design of insulator, high-handed electric, circuit control and pneumatic drive. By means of test and verify, it was proved that the product could completely meet the requirements of EMUs in extremely-cold circumstance.